Under Construction: One State's Approach to Creating Health Homes for Individuals with Serious Mental Illness - Andrea M. Auxier; Bonni D. Hopkins; Anne E. Reins (AIMS Press, 2015)
Changes to the health care market associated with the Patient Protection and Affordable Care Act (ACA) are creating both need and opportunity for states, health plans, and providers to improve quality, outcomes, and satisfaction through better integration of traditionally separate health care delivery systems. Applications of the term "integrated care" vary widely and include, but are not limited to, the integration of care for Medicare-Medicaid dually enrolled beneficiaries, the integration of mental health and substance abuse (also known as behavioral health), and the integration of mental health and substance abuse with medical care, most commonly primary care. In this article, integrated care refers to well-coordinated physical health and behavioral health care. Medicaid Health Homes are emerging as a promising practice, with sixteen states having adopted the Health Home model through approved State Plan Amendments. This article describes one state's journey towards establishing Health Homes with a behavioral health focus. We discuss a partnership model between the relevant state organizations, the contracted providers, and the behavioral health managed care organization responsible for many of the supportive administrative functions. We highlight successes and operational challenges and offer recommendations for future Health Home development efforts.